ACİL SERVİSTE AKUT KARIN TANISI DÜŞÜNÜLEN HASTALARIN AYIRICI TANISINDA 5-HİDROKSİ İNDOL ASETİK ASİT VE SENSİTİF C-REAKTİF PROTEİN'İN YERİ - GEDİKLİ, ALAATTİN (Fırat Üniveristesi, 2006)
Akut karın ağrısı, travmaya bağlı olmayan, kendiliğinden oluşan, ana semptomukarın ağrısı olan, sıklıkla acil cerrahi müdahale gerektiren ve bir haftadan daha kısa sürelikarın ağrıları olarak tarif edilebilir. Akut karınlı hastaların değerlendirilmesi ve tedavisiaşamalarında klinisyenler için birçok zorluklar bulunmaktadır. Akut karın ağrısı, acilserviste (AS) sık görülen altında birçok neden bulunan yaygın şikayetlerdendir. Buçalışmada amaç spot idrarda 5-hidroksi indol asetik asit (5-HIAA) ve serum sensitif C-reaktif proteinin akut karın ağrısının ayırıcı tanısındaki değerini bulmaktı.Fırat Üniversitesi Tıp Fakültesi (FÜTF) AS'ye Ocak-Ekim 2005 tarihleri arasındaakut karın ağrısı şikayetiyle başvuran 140 hasta, yazılı veya sözlü onayları alınarakçalışmaya dahil edildi. Bu hastalardan 110'una akut batın, 30'una non-spesifik karın ağrısı(NSAP) tanıları konuldu. Hastalardan alınan spot idrar örneğinde 5-HIAA düzeyi,başvurunun ilk saati içinde Eliza yöntemi ile bakıldı. Eş zamanlı alınan kan örneğinden eldeedilen serumda, yüksek duyarlılıklı C-reaktif protein (hsCRP) nefelometrik yöntemleölçüldü5-HIAA değerleri açısından akut karın ve NSAP'li grup, kontrol grubuna göreanlamlı bir artış izlendi (p<0,05). Ancak akut karın ve NSAP'si bulunan hastalar arasındaanlamlı bir fark yoktu (p>0,05). Akut karın grubu ile kontrol grubu karşılaştırıldığındahsCRP değerlerinin akut karın lehine anlamlı düzeyde artış gösterdiğini (p<0,05), ancakNSAP'si olan hastaların kontrol grubuyla karşılaştırıldığında sonucun anlamlı olmadığınıbulduk (p>0,05). Çalışmamızda, hsCRP için sensitivite % 90,4, spesifite %18.7, 5-HIAAiçin ise sırasıyla % 92 ve %10 olarak bulduk.Serum hsCRP ölçümü akut karın tanısı koymada yardımcı bir yöntemdir fakatspesifisitesinin düşük olması tanı değerini azaltmaktadır. Spot idrarda 5-HIAA ölçümü karınağrılı hastaların ayırıcı tanısı için kullanımı faydalı değildir. Bu konuda yapılacak ilaveçalışmalara ihtiyaç olduğunu düşünmekteyiz.Anahtar kelimeler: Karın ağrısı, acil servis, ayırıcı tanı, hsCRP, 5-HIAA

VALUE OF THE DIFFERENTIAL DIAGNOSIS OF PATIENTS WITH ACUTEABDOMINAL PAIN OF SERUM SENSITIVE C-REACTIVE PROTEIN AND 5-HYDROXYINDOLACETIC ACID IN EMERGENCY DEPARTMENTAcute abdominal pain is usually defined as the onset of abdominal pain of less than oneweek?s duration, unrelated to trauma and the main symptom is abdominal pain that requiressurgical intervention. The evaluation of patients with acute abdominal pain can be one of the mostdifficult challenges for the clinician. Acute abdominal pain is a common presenting symptom inthe emergency department and has many underlying causes. The aim of this study was to assessvalue of the differential diagnosis on acute abdominal pain of serum sensitive C-reactive protein(hsCRP) and 5-hydroxyindolacetic acid (5-HIAA).The study was conducted in Firat University Faculty of Medicine emergency department atJanuary-October 2005. One hundred forty adult patients who presented to emergency departmentof the university hospitals with acute abdominal pain participated in this study. Written and verbalinformed consent was obtained from the participants before their inclusion in the study. 110 ofthese patients were diagnosed as acute abdominal pain and 30 patients were nonspecific abdominalpain. 5-HIAA was measured by ELISA in the spot urine samples of 140 patients within the firsthour of admission. Serum obtained through blood samples taken at the same time, measurementsof hsCRP were performed by using nephelometry method.There was significant difference in the value of 5- HIAA in the group with acute abdominalpain and nonspecific abdominal pain compare to the control group (p<0,05). However, there wasnot a significant difference between the patients with acute abdominal and patients with thenonspecific pain (p>0,05). In addition, there was significant difference in the hsCRP valuebetween the patients with acute abdominal pain and the control group (p<0,05). But, there was nota significant difference in the hsCRP value between patients with the nonspecific pain and thecontrol group (p>0,05). The sensitivity and specificity was found 90,4%, 18,7% for hsCRP and92%, 10% for 5-HIAA, respectively.The results showed that hsCRP is important method for the diagnosis of the acuteabdominal pain but the value of diagnosing decreases since the specificity is low. Measurement of5-HIAA in spot urine is not helpful in the differential diagnosis of acute abdominal pain. Weconsider that this result warrants further research.Key words: Abdominal pain, emergency department, differential diagnosis, hsCRP, 5-HIAA1
Value of the differential diagnosis of patients with acute abdominal pain of serum sensitive C-reactive protein and 5-hydroxyindolacetic acid in emergency department
Keywords: İlk ve Acil Yardım